Pengaruh Kompensasi Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT Electronic City Indonesia Tbk Cabang Tangerang - Amalia, Nana; Priadi, Andri (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstrak. This research aims to analyze the influence of compensation and job satisfaction on employee performance at PT Electronic City Indonesia, Tangerang Branch. The research method used is quantitative with a descriptive associative approach. The population in this study consists of all employees totaling 63 people, and the sampling technique used is total sampling or census. Data collection was conducted through questionnaires, and data analysis techniques included simple and multiple linear regression as well as hypothesis testing (t-test and F-test). Compensation has a positive and significant partial effect on employee performance, with a regression coefficient of 0.677 and a contribution of 55.0%. Job satisfaction also has a positive and significant partial effect on employee performance, with a regression coefficient of 0.777 and a contribution of 61.2%. Simultaneously, compensation and job satisfaction have a positive and significant influence on employee performance, with the multiple regression equation Y = 10.946 + 0.094 X1 + 0.687 X2. The coefficient of determination (R²) is 0.564 or 56.4%, indicating that 56.4% of employee performance is influenced by both variables, while the remaining 43.6% is influenced by other factors outside the study.Thus, compensation and job satisfaction are proven to have a significant effect, both partially and simultaneously, on improving employee performance at PT Electronic City, Tangerang Branch. Keywords: Compensation, Job Satisfaction, Employee Performance